The Future of Health Care: Going to the Dogs? - Freeman, William D.; Vatz, Kenneth A. (Frontiers in Neurology, 2015)
Escalating healthcare expenditures, which already represent 16% of the United States’ gross domestic product (GDP), necessitate redesign of contemporary health care delivery modalities. One such model uses non-human employees (NHE) such as the Canis domesticus, which can potentially lower costs, provide sensitive detection of nosocomial pathogens, alert physicians and other caregivers to impending seizures, and provide comfort to patients. We propose consideration of canine NHE for appropriate clinical situations, but acknowledge the various limitations and caveats.